A narrative review of the economic burden of myelin oligodendrocyte glycoprotein antibody-associated disease and analogous conditions - Lee, Leonard; Byrnes, Joshua; Hope, Cathryn; Kim, Hansoo (Frontiers in Neurology, 2025)
BackgroundMyelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is an inflammatory demyelinating disease of the central nervous system with a serious, debilitating presentation, including residual disability after relapses.ObjectivesTo evaluate the economic impacts of MOGAD and analogous conditions, including direct costs, indirect costs and cost drivers.DesignSystematic literature search and narrative review.Data sources and methodsSearch strings were designed to capture any study reporting health economic impacts of MOGAD or analogous autoimmune diseases of the nervous system. The costs of diagnostic tests and short- and long-term interventions were considered, and studies from both patient and institutional (public and private) perspectives were included. Searches were conducted using medical subject headings (MeSH) in PubMed in July 2023. Retrieved publications were screened initially based on title and abstract, then based on the full text. Data were extracted manually; findings are reported descriptively. All cost data were adjusted to 2024 US Dollars using the CCEMG-EPPI-Centre Cost Converter.ResultsResults from 40 studies of MOGAD and analogous autoimmune neurological conditions were extracted. In the only study that included patients with MOGAD (a cost investigation from Germany in which 166 patients had neuromyelitis optica spectrum disorder and 46 had MOGAD), the mean annualised cost of illness was 94,688 (direct medical costs 43%, direct non-medical costs 34%, indirect costs 23%). Across the conditions assessed, the annual total cost of illness per patient ranged widely, from 3,690 to 507,117 (among studies that reported types of cost, the range for direct costs was 1,981–148,388; for indirect costs, 0–942,707). The study that included patients with MOGAD identified the need for care, number of acute attacks, unemployment and disability as independent predictors of cost. Additional cost drivers (from all the conditions) included treatments (e.g., intravenous immunoglobulin), hospitalisation, disease severity, relapses and refractory disease.ConclusionOur search identified only one study that specifically examined costs associated with MOGAD. Results from this and studies of analogous autoimmune conditions suggest that inflammatory demyelinating diseases of the central nervous system including MOGAD are costly for the individual patient and place considerable burden on healthcare systems. Further evidence is needed for increased insight into the economic burden of MOGAD.